Problem aspects of staff formation of specialized anti-corruption prosecutor’s office - Demkiv, Denys (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article is devoted to the problem aspects of the Specialized Anti-Corruption Prosecutor’s Office staff formation on the basis of the analysis of the theoretical and legal foundations of the current Ukrainian legislation and generalizations of its practical realization. The features of the staff formation system of the Specialized Anti-Corruption Prosecutor’s Office are determined. The directions of solving the problem aspects of staff formation of the Specialized Anti-Corruption Prosecutor’s Office are offered